Computer‐aided drug design to explore cyclodextrin therapeutics and biomedical applications. (February 2017) - Abdolmaleki, Azizeh; Ghasemi, Fatemeh; Ghasemi, Jahan B.
Abstract : Cyclodextrin (CD) is a subset of the macrocyclic structural class, which is an important class of small organic agents that are useful functional excipients. They have wide range application possibilities in different fields of sciences such as material preparation, medicine, analytical chemistry, and separation processes. They are used widely in pharmaceutical formulations and drug delivery for increasing the water solubility of low soluble drugs and drug candidates. Due to the ring structure, they behave differently than smaller molecules and may be capable of hitting new classes of targets. A macrocyclic molecule presents varied functionality and stereochemical complexity in a pre‐organized conformation of the ring structure. This can result in high selectivity and affinity for protein targets while conserving enough bioavailability to arrive at intracellular locations. Regardless of these valuable features, and the verified success of several marketed macrocycle drugs isolated from natural compounds, this class has been little explored in drug development. This study describes some of the key features of the CDs therapeutic discovery. Also, the application of computational chemistry approaches such as QSAR/QSPR, molecular docking, and molecular/quantum mechanics for modeling of CD–drug system is reviewed briefly. Abstract : Computational chemistry approaches such as QSAR/QSPR, molecular docking, and molecular/quantum mechanics for modeling of the CD–drug system have been discussed. A summary of recent findings on computer‐aided methods that are logically successful to discover/prediction of interactions between drug–CDs and have shown promising potential in facilitating drug design.